Cafeteria diet increases liquid intake and serum creatinine levels in rats - Roberta Ströher; Isabel Cristina de Macedo; Carla de Oliveira; Vanessa Leal Scarabelot; Tizye Lima Rizzo; Jeferson Ferraz Goularte; Wolnei Caumo; Adriane Belló Klein; Gilberto Luiz Sanvitto; Iraci LS Torres (Clinical and Biomedical Research, 2017)
Introduction: Important changes in human dietary pattern occurred in recent decades. Increased intake of processed foods leads to obesity, which is related with the development of chronic diseases such as type 2 diabetes mellitus, hypertension, as well as cardiovascular and chronic kidney diseases. The prevalence of hypertension has also dramatically increased in recent years, and high sodium intake contributes to this scenario. In healthy individuals, kidneys are the primary end-organs that regulate sodium homeostasis. This study aims to evaluate renal function parameters and systolic blood pressure measurements in an animal model of obesity.